1994
DOI: 10.1103/physrevb.49.15416
|View full text |Cite
|
Sign up to set email alerts
|

Energy gap of the high-TcsuperconductorHgBa2

Abstract: Tunneling spectra of a polycrystalline bulk HgBa&Ca2Cu308+& with T, = 132 K have been measured by point-contact spectroscopy using a low-temperature scanning tunneling microscope. Unlike other high-T, superconductors the conductance of this material shows a BCS-like gap structure with a relatively small smearing parameter I'. Conductances with a linear density of states for IeVI ( b, and a small cusp at the gap are also observed. From a simple calculation based on the assumption that the surface is covered wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The STM tunneling data for the Hg cuprates reported in this work are indicated by solid circles and underlined labels. STM tunneling data from previous works 42,47 are indicated by open circles. The break-junction tunneling data on BSCCO, YBCO, its 60 K phase ͑YBCO-60 K͒ and La 2Ϫx Sr x CuO 4Ϫx ͑LSCO͒ are indicated by solid squares.…”
Section: Data Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STM tunneling data for the Hg cuprates reported in this work are indicated by solid circles and underlined labels. STM tunneling data from previous works 42,47 are indicated by open circles. The break-junction tunneling data on BSCCO, YBCO, its 60 K phase ͑YBCO-60 K͒ and La 2Ϫx Sr x CuO 4Ϫx ͑LSCO͒ are indicated by solid squares.…”
Section: Data Interpretation and Discussionmentioning
confidence: 99%
“…41 Jeong et al, observed two types of spectra, one BCS-like with a large gap and the other showing heavily smeared double-gap features, in polycrystalline Hg-1223 by scanning tunneling spectroscopy ͑STS͒. 42 Rossel et al also observed smeared gap spectra by STS in melted polycrystalline Hg-1223, but enhanced-peak spectra with very large gap values in single crystals of Pb-doped Hg-1234. 43 Differences in sample quality and measurement technique could have contributed to this spectral variety.…”
Section: Introductionmentioning
confidence: 92%
“…|ε b | and g have to be obtained from Eqs. (60,63,65) (with n B = 0, C a = C a0 and ε A0 = −∆). The situation ∆/T c = 4 corresponds to the critical case described in Section VI G.…”
Section: B Tunneling Characteristicsmentioning
confidence: 99%
“…The line has been prepared on the basis of the formula (1). The experimental data: (a) Jeong et al[60], (b) Rossel et al[61].…”
mentioning
confidence: 99%